Narrative Strategien in der TV-Serie Desperate Housewives - Marion Fuchs (Current Objectives of Postgraduate American Studies, 2012)
The TV-series Desperate Housewives is desperately loved by fans and desperately hated by critics. American columnist Jennifer L. Pozner accuses the series of portraying every female character as incompetent, in her opinion that is "just good old fashioned Hollywood crap." But why is this "Hollywood crap" so astonishingly successful (25 million viewers in the US, 3 million viewers in Germany) and who is the typical viewer? Why is the (dead) narrator so important and does the TV-Series really reinforce old-fashioned stereotypes or does it present modern, independent housewives? These questions are the main focus of this essay and shall be answered by analyzing typical visual and narrative strategies of the series.